Analysis of household crop commercialization in Nigeria - Olanike Alawode , Olubunmi; Lekan Makinde, Olumuyiwa (Applied Studies in Agribusiness and Commerce, 2021)
Nigeria is experiencing a gradual shift from subsistence to commercialized agriculture, thereby increasing involvement and activities at different nodes of agribusiness. Participation of farmers in markets is an important determinant of well-being and development, and one of the pathways towards economic growth. This study analysed household crop commercialization in Nigeria. The secondary data used were the General Household Survey (GHS, 2018) Wave 4. Data were analysed using descriptive statistics, household crop commercialization index (HCCI) and ordered probit regression model.Mean age of Nigerian farmers was 50.04 years (±15.22), majority (85.68%) were male, married (82.51%), and 72.14% had formal education. Farming is viable in all the geopolitical zones and majority (87.64%) of the farmers were from the rural sector, holding a mean total plot size of 12.61(±15.63) hectares, and planted 3 crops on the average. The most produced crop categories are cereals (46.75%), tubers (20.70%) and legumes (19.00%); legumes and cereals are highest in the North, and tubers in the South. Subsistence households were 32.81% (HCCI=0), only 1.71% of the households were fully commercial (HCCI=100), while semi-subsistence households (0≤HCCI≤100) constitute 65.48%. Years of education (p